Long-Term Global and Focal Cerebral Atrophy in Perimesencephalic Subarachnoid Hemorrhage—a Case–Control Study - Gama Lobo, G (2022)
Purpose: Non-aneurysmal perimesencephalic subarachnoid hemorrhage (PmSAH) represents 6.8% of spontaneous subarachnoid hemorrhage, and usually has a benign clinical course. However, patients might have early cerebral ischemic lesions and long-term neurocognitive complaints. Cerebral atrophy has been described in patients after aneurysmal SAH, but not in PmSAH. We aimed to investigate if PmSAH associates with increased brain volume loss. Methods: In this prospective study, we included consecutive patients with PmSAH that performed MR in the first 10 days after hemorrhage, and follow-up MR 6-7 years later. Automated volumetric measurements of intracranial, white matter, gray matter, whole brain, lateral ventricles, hippocampus, and amygdala volumes were performed. Volumes were compared to a normal population, matched for age. Results: Eight patients with PmSAH were included, with a mean age of 51.5 (SE 3.6) at baseline. The control group included 22 patients with a mean age of 56.3 (SE 2.0). A relative reduction of all volumes was found in both groups; however, PmSAH patients had significant reductions in intracranial, white and gray matter, whole brain, and hippocampal volumes when compared to controls. These changes had a higher magnitude in whole brain volume, with a significant absolute decrease of 6.5% in PmSAH patients (versus 1.9% in controls), and a trend for an increase in lateral ventricle volume (absolute 21.3% increase, versus 3.9% in controls). Conclusion: Our cohort of PmSAH patients showed significant long-term parenchymal atrophy, and higher global and focal parenchymal volume loss rates when compared to a non-SAH population.